A Novel Method for Better Bacterial Genome Assembly from Illumina Data - Ni, Peixiang; Dai, Wenkui; Liu, Yongfeng; Yang, Zhenyu; Zhou, Tao; Liang, Shuqing; Wang, Tong; Xu, Jing; Zhao, Yun (Current Bioinformatics, 2017)
Background: With the rapid development of next generation sequencing technology, a great many individual genomes have been generated. Genome sequence of bacterium, as the foundation of microbiology research, is of great value. Due to the diversity and complexity of bacterium, assembling genome short reads is still challenging. Objective: A new solution has been developed based on SOAPdenovo assembler to increase the fineness and accuracy of bacterial genome sequence. Method: The method mainly contains four steps: preliminary genome assembly via SOAPdenovo, super scaffold construction, gap closure and final sequence revision. Results: Seventeen fine genomes have been generated through this solution. Meanwhile, 23 sequenced strains are chosen to evaluate the advantage of this method, and the assembly result shows that 16 of them are better than the original ones in contiguity and accuracy. Conclusion: With more and more individual bacterial genomes generated by this method, we can infer that this work provides a cost-effective and time-saving method for the acquisition of bacterial genomes.
Keywords: SOAPdenovo